Discrete choice modelling of labour supply in Luxembourg through EUROMOD microsimulation - Frédéric Berger; Nizamul Islam; Philippe Liégeois (University of Essex, Institute for Social and Economic Research (ISER), 2010)
In this study, the household labour supply is modelled as a discrete choice problem assuming that preference for leisure and consumption can be described by a quadratic utility function which allows for non-convexities in the budget set. We assess behavioural responses to the significant changes in the taxbenefit system during 2001-2002 in Luxembourg. Only moderate impact is found, on average, on the efficiency of the economy as measured by the labour supply effects. The impact is indeed concentrated on richer single women. These increase significantly their labour force, which more than doubles the nonbehavioural effect of the tax reform on disposable income and boosts the gains in well-being for that part of population.
Keywords: C25; H24; H31; J22; 330; Labour supply; Discrete choice; Households; EUROMOD; Microsimulation; Tax reform; Arbeitsangebot; Offenbarte Präferenzen; Freizeit; Konsum; Steuerreform; Verhaltensökonomik; Simulation; Luxemburg